Analysis of Internal Factors Influencing Interest in Becoming A Teacher in Economics Education Students of UIN Sultan Syarif Kasim Riau - Niken Ayu; Ansharullah Ansharullah; Dicki Hartanto (Universitas Islam Negeri Sultan Syarif Kasim Riau Pekanbaru, 2023)
This research aimed at finding out internal factors influencing very muchstudent interest in becoming teachers at Economics Education Department of Education and Teacher Training Faculty of State Islamic University of Sultan Syarif Kasim Riau Pekanbaru. It was an analysis research with quantitative approach. The subjects of this research were 156 Economics Education Department students of 2019. Simple random sampling technique was used in this research. Questionnaire and documentation were the techniques of collecting data. The technique of analyzing data was factor analysis. Based on the analysis result, it could be concluded that the internal factors influencing student interest in becoming teachers at Economics Education Department of Education and Teacher Training Faculty of State Islamic University of Sultan Syarif Kasim Riau Pekanbaru were teacher duty, the knowledge of teacher profession, and teacher title prestige/response.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//